The Brain finds a leg - Chatterton, Martin (Atlanta [Ga.] : Peachtree, 2009)
In Farrago Bay, Australia, thirteen-year-old Sheldon is recruited by a new student, Theo Brain, to help investigate a murder, which is tied not only to bizarre animal behavior but also to a diabolical plot to alter human intelligence.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Originally published: Surry Hills, N.S.W. : Little Hare ; London : Bounce! [distributor], 2007.
Keywords: Intellect -- Juvenile fiction; Animal behavior -- Juvenile fiction; Inventions -- Juvenile fiction; Schools -- Juvenile fiction; Australia -- Juvenile fiction; Intellect -- Fiction; Animal behavior -- Fiction; Inventions -- Fiction; Schools -- Fiction; Australia -- Fiction; Mystery and detective stories; Humorous stories